Collections for the Public Good: A Case Study from Ohio - Loren E. Babcock; Daniel F. Kelley; John B. Krygier; William I. Ausich; David L. Dyer; Dale M. Gnidovec; Anne M. Grunow; D. Mark Jones; Erica Maletic; Camilla Querin; H. Gregory McDonald; D. Joseph Wood (Diversity, 2025)
Natural history collections serve science and society in a variety of ways. Collections of geological, including paleontological, materials are of special importance in the 21st century, as they serve not only as repositories for scientific research specimens, but are also used in teaching, outreach, and engaging the public in science. These collections link us to our scientific, technological, and cultural history, and help to inspire the next generations of scientists and technologists. In addition, they provide inspiration for creative works. They also have an important role in informing public policy and national security, as geological materials are fundamental to the global economy. Examples from universities, museums, and government agencies in central Ohio, USA, help to illustrate the myriad ways that geological collections are relevant to modern society, and provide continuing, critical benefits. These examples reinforce the need to ensure the long-term support of collections.